(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Ensuring access to vaccines, therapeutics and diagnostic is a crucial tool in the fight against public health crises. However, international norms on intellectual property rights, however, set limits to the distribution of these products. Despite the lessons learned from the COVID-19 pandemic, within the negotiation of a new ‘pandemic agreement’, led by the World Health Organization, remains fraught with divergent positions among countries on how to derogate from IPR norms. The paper suggests that, without taking into account international human rights law, the reform risks being ineffective with regard to its main objective: the universal protection of health.